Optimisasi Efisiensi Kehadiran Pegawai Melalui Sistem Presensi Berbasis Web Dengan Metode Scrum di KPU Provinsi Papua Tengah - Arfan, Usman; Murib, Yance (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Employee attendance efficiency is an important factor in increasing work productivity. KPU Central Province is still using a manual attendance system that is prone to errors and data falsification. How to build a web-based attendance system that can improve employee attendance efficiency at KPU Central Province? Implementing an efficient and integrated web-based attendance system with the Scrum method to improve employee attendance efficiency at KPU Central Province. This research uses the Scrum development method in the system development process. The development of a web-based attendance system successfully increases the efficiency of employee attendance at KPU Central Province. The web-based attendance system integrated with the Scrum method is proven to reduce attendance time and improve the accuracy of attendance data. A web-based attendance system with the Scrum method is an effective solution to improve employee attendance efficiency at KPU Central Province. This system is proven to be more accurate, efficient, and integrated with the work process. The implementation of this system needs to be accompanied by training and socialization for employees. Regular system upgrades and development can be done to optimize system performance